Resistance to Change and Organizational Culture among Managers in a Mass Consumption Company from Lima - Pacheco Lenti, Ariana Vanessa (2023)
The COVID-19 pandemic is one of the greatest crises ever faced by the human race, generating unprecedented transformations which have required the development of adaptability and flexibility in all contexts. Organizations worldwide were forced to change in order to respond to the new challenges from their environment and remain in the market. This is why it is necessary for organizations and the individuals who are part of them to be prepared to conduct transformation processes. This is particularly true of managers, whose attitudes toward change can determine the success or failure of these processes, as they directly influence their employees' motivation and participation. The main aim of this study was to determine the relationship between resistance to change and organizational culture among managers in a mass consumption company from Lima. This was a non-experimental, cross-sectional and correlational-causal study. The sample was made up of 25 first- and second-line managers in the organization leadership. The results of this research determined that resistance to change is not related to organizational culture.